Laser photo-ionization study of natAg using opto-galvanic signal at SPES offline laser lab. (1st December 2022) - Khwairakpam, O.S.; Mariotti, E.; Scarpa, D.; Nicolosi, P.; Khanbekyan, A.; Arzenton, A.; Ferracane, S.; Andrighetto, A.
Abstract: Resonant Ionization Laser Ion Source (RILIS) is one of the most advancing techniques for the production of radioactive ion beams (RIBs) in ISOL facilities. SPES project at INFN-LNL is a second generation ISOL facility which aims to produce several isotopes in a couple of years. Within the framework of this project, resonant photo-ionization schemes of several elements are studied in the offline laser lab, to be later implemented in the SPES Laser Ion Source. Silver is one of the elements being studied for the stated purpose. In this article, we report a resonant photo-ionization scheme of silver tested with a hollow cathode lamp (HCL). Evidence of high lying Rydberg states around 60945.32 cm −1 has also been observed by studying the fast opto-galvanic signal detected.